Miles morales: spider-man (2022), volume 1 ebook Trial by spider. - Ziglar, Cody (Miles Morales: Spider-Man (2022), 2023)
Collects Miles Morales: Spider-Man (2022) #1-5. Someone's not walking away from this one! Spider-Man faces the strongest super-powered foes and most dangerous gauntlets the Multiverse can throw his way. And every time Miles Morales falls, he rises again - stronger than before. Until now. There are some punches you don't get up from, and a new villain isn't pulling a single one as they threaten everyone and everything Miles loves. Between school, home, his love life and fighting crime night and day, Miles is reaching his breaking point. And when this new foe is finished, Spider-Man's world will be changed forever! But what does this villain have to do with Misty Knight's investigation and a slew of upgraded foes, like the souped-up Scorpion, terrorizing NYC?